2015
DOI: 10.1155/2015/242158
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 Target Genes in the Early Phase of Long-Term Potentiation in the Rat Hippocampal CA1 Area

Abstract: Gene expression plays an important role in the mechanisms of long-term potentiation (LTP), which is a widely accepted experimental model of synaptic plasticity. We have studied the expression of at least 50 genes that are transcriptionally regulated by p53, as well as other genes that are related to p53-dependent processes, in the early phase of LTP. Within 30 min after Schaffer collaterals (SC) tetanization, increases in the mRNA and protein levels of Bax, which are upregulated by p53, and a decrease in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Indeed, GA directly binds E1 and inhibits the formation of E1-SUMO intermediate at the same range of concentrations here used to prevent LTP inhibition by Aβ (Fukuda et al, 2009). In addition, GA can also inhibit the SUMOylation of p53 (Fukuda et al, 2009), which is known to play a crucial role in the early phase of LTP (Pustylnyak et al, 2015) and has been shown to be involved in aging and AD (LaFerla et al, 1996; Lanni et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GA directly binds E1 and inhibits the formation of E1-SUMO intermediate at the same range of concentrations here used to prevent LTP inhibition by Aβ (Fukuda et al, 2009). In addition, GA can also inhibit the SUMOylation of p53 (Fukuda et al, 2009), which is known to play a crucial role in the early phase of LTP (Pustylnyak et al, 2015) and has been shown to be involved in aging and AD (LaFerla et al, 1996; Lanni et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The increase in p53 DNA-bound fraction was not associated with the increase in total p53 protein, which suggests p53 activation was due to post-translational modifications. The total p53 protein level even decreased in the area CA1 20 min after LTP induction, while p53 mRNA level did not change [60]. Therefore, the p53 protein degradation accelerated or/and p53 mRNA translation slowed in the early phase of LTP.…”
Section: Ltp-associated Expression Of S100b and Other P53 Target Genementioning
confidence: 88%
“…We used chromatin immunoprecipitation to study р53 binding to three loci in S100B promoter with pREs within them (Figure 1). The p53 binding to all these sites in S100B promoter strongly correlated with S100B mRNA dynamics in a time window 10-40 min after SC tetanization [60]. Interestingly, the p53 binding to the conserved site was most expressed.…”
Section: Ltp-associated Expression Of S100b and Other P53 Target Genementioning
confidence: 92%
See 1 more Smart Citation
“…This Mdm2-p53-Akt signaling represents a unique pathway for Gp1 mGluRdependent plasticity mechanisms. Mdm2-p53 signaling had not been shown to regulate neuronal plasticity until recently (Jewett et al, 2015(Jewett et al, , 2016Lisachev et al, 2015;Pustylnyak et al, 2015), and still little is known about p53 signaling in the central nervous system. Our current study introduces a novel function of p53 in the regulation of activity-dependent neural network plasticity.…”
Section: Introductionmentioning
confidence: 99%